Young people’s job-search strategies in the German apprenticeship market: Who relies on referrals by strong ties and why? - Flohr, Matthias [Verfasser]; Protsch, Paula [Verfasser] (My University, 2022)
„Social capital is often regarded as an important resource when searching for a job. However, unlike in the general labor market, in youth labor markets, leveraging network contacts does not necessarily enhance young people’s chances compared to formal job-search methods. Who then uses referrals by strong ties to support their school-to-work transitions? Drawing on the German National Educational Panel Study, we focus on noncollege-bound students searching for apprenticeship places. We investigate whether parental referrals are more likely to be used as a compensation strategy for limited opportunities due to regional conditions and lower levels of schooling and whether this search strategy entails a trade-off in terms of higher dropout risks. Our results indicate that in regions with poor regional labor market conditions, young people use parental referrals more often and also increasingly find apprenticeship places via referrals. Moreover, using referrals does not result in higher dropout risks. Lower-educated school leavers are also more likely to use referrals but they do not benefit from this search channel more than higher-educated youth. We conclude that social contacts can at least partly compensate for poor opportunities due to regional market conditions.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; 370; 300; Ausbildungsstellenmarkt; Ausbildungsplatzsuche; Ausbildungsstellenbewerber; Bewerbungsverhalten; Empfehlung; Regionale Disparität; Nationales Bildungspanel